Association of personal and systemic factors on intrapartum risk perception and obstetric intervention rates: a cross-sectional study - Nina H Peterwerth; Margareta Halek; Rainhild Schäfers (BMC, 2024)
Abstract Background Risk perception is fundamental to decision-making; therefore its exploration is essential to gaining a comprehensive understanding of the decision-making process for peripartum interventions. The aim of this study was to investigate associations between personal and systemic factors of the work setting and the risk perception of obstetric healthcare professionals, and in turn how this might influence decisions regarding obstetric interventions. Methods Case vignettes were used to measure risk perception. A quantitative cross-sectional online survey was performed within an exploratory sequential mixed-methods design, and an intervention readiness score created. Associations were calculated using location and dispersion measures, t-tests and correlations in addition to multiple linear regression. Results Risk perception, as measured by the risk assessment score, was significantly lower (average 0.8 points) for midwives than for obstetricians (95%-CI [-0.673; -0.317], p < .001). Statistically significant correlations were found for: years of experience and annual number of births in the current workplace, but this was not clinically relevant; hours worked, with the groups of participants working ≥ 30,5 h showing a statistically significant higher risk perception than participants working 20,5-30 h (p = .005); and level of care of the current workplace, with the groups of participants working in a birth clinic (Level IV) showing a statistically significant lower risk perception than participants working in Level I hospital (highly specialised obstetric and neonatal care; p = .016). The option of midwife-led birthing care showed no correlation with risk perception. The survey identified that risk perception, occupation, years in the profession and number of hours worked (i.e. full or part time) represent significant influences on obstetric healthcare professionals' willingness to intervene. Conclusions The results of the survey give rise to the hypothesis that the personal and systemic factors of professional qualification, occupation, number of hours worked and level of acuity of the workplace are related to the risk perception of obstetric healthcare professionals. In turn, risk perception itself made a significant contribution to explaining differences in willingness to intervene, suggesting that it influences obstetricians' and midwives' decision-making. Overall, however, the correlations were weak and should be interpreted cautiously. The significant variations in the use of interventions must be addressed in order to provide the highest quality and best possible care for childbearing women and their families. To this end, developing strategies to improve interdisciplinary relationships and collaboration is of great importance. Trial registration German Clinical Trials Register DRKS00017172 (18.06.2019).